The Effectiveness of the 20-20-20 Rule in Managing Computer Vision Syndrome among Workers: A Systematic Review - Retti Dwitria Wilda; Henny Permatasari; Utami Rachmawati (Indonesian Journal of Global Health Research, 2025)
Computer Vision Syndrome (CVS) is a condition that often occurs in individuals who spend long periods of time in front of a computer screen or other digital devices. Common symptoms include eye strain, visual fatigue, blurred vision, and headaches. The increasing use of digital devices among workers can cause computer vision syndrome (CVS) and lead to decreased work productivity. The 20-20-20 Rule is a non-pharmacological intervention that is believed to be effective in treating computer vision syndrome (CVS). This study examines research findings on the effectiveness of the 20-20-20 Rule in treating computer vision syndrome (CVS) among workers. This study used a Systematic Review method. The articles used were sourced from PubMed, ProQuest, ScienceDirect, Scopus, Cochrane, published between 2018-2024. The search technique followed the PRISMA method. The search identified five articles that met the inclusion and exclusion criteria. Based on these findings, Rule 20-20-20 is effective in overcoming computer vision syndrome (CVS) in workers. Rule 20-20-20 can be used as a nursing intervention to overcome computer vision syndrome (CVS) in workers.